The Effect of Brain-Based Feedback on Cognitive Load and Affective Factors among EFL Learners: Anxiety, Enjoyment, and Motivation - Jafari Mehr , Samaneh; Fatehi Rad, Neda; Shahabi , Hassan (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: This study aimed to investigate the effects of brain-based feedback on perceived cognitive load and key affective factors, including foreign language anxiety, foreign language enjoyment, and second-language motivation, among intermediate EFL learners. Methods and Materials: A quasi-experimental pretest–posttest design with a control group was employed. The participants were 60 intermediate EFL learners who were assigned to an experimental group receiving brain-based feedback and a control group receiving traditional corrective feedback. The intervention was implemented over eight weeks. Grounded in Cognitive Load Theory and Control-Value Theory, brain-based feedback was designed to align feedback delivery with learners’ cognitive processing capacity and emotional responses. Data on perceived cognitive load, foreign language anxiety, enjoyment, and second-language motivation were collected before and after the intervention. Inferential statistical analyses were conducted to examine time, group, and time-by-group effects on the study variables. Findings: A statistically significant time-by-group interaction was found for perceived cognitive load, F(1, 58) = 40.40, p < .001, ηp² = .41, indicating a substantially greater reduction in cognitive load in the experimental group than in the control group. Significant time-by-group interaction effects were also obtained for the affective variables, with partial eta-squared values ranging from .24 to .49. These effects demonstrated that participants receiving brain-based feedback experienced significantly greater reductions in foreign language anxiety and significantly greater increases in foreign language enjoyment and second-language motivation compared with learners receiving traditional corrective feedback. Conclusion: Brain-based feedback appears to be an effective instructional approach for simultaneously reducing learners’ perceived cognitive demands and improving their affective experiences in EFL classrooms. Aligning feedback with learners’ cognitive processing capacities and emotional needs may create more supportive learning conditions, reduce anxiety, and strengthen enjoyment and motivation. These findings highlight feedback as a targeted neuroscience-informed mechanism through which classroom practices can influence learners’ internal cognitive and emotional conditions.